Emulsion polymerization of N-halamine polymer for antibacterial polypropylene. Issue 15 (September 2016) - Du, Jinmei; Luo, Xiongfang; Zhang, Li; Liu, Yin; Li, Rong; Ren, Xuehong; Huang, Tung-Shi
N -halamines are highly efficient antibacterial agents. They can inhibit or inactivate bacteria by transformation of the N-Cl bond to an N-H bond, and be regenerated by chlorination. In this study, regenerable biocidal poly(VAc-co-MAM) was synthesized by emulsion polymerization with vinyl acetate (VAc) and methacrylamide (MAM). Polymerization was optimally carried out at 100℃ for 7 hours using a 10:1 molar ratio of VAc to MAM in the presence of 1% initiator in mass to the total of VAc and MAM. The synthesized polymer emulsion was used for antibacterial treatment of polypropylene (PP) nonwoven fabric. The treated fabric was found to have an active chlorine value of 0.21%, which exhibited excellent antibacterial activity. The active group N-Cl in PP fabric treated with poly(VAc-co-MAM) was unstable under ultraviolet irradiation, but could be recovered through chlorination. Poly(VAc-co-MAM) can be used as an antibacterial agent for many other fibers, not limited to PP, since it has a hydrocarbon chain that provides a good compatibility with other synthesized fibers through the Coulomb force and hydrophobic bond.